PENGEMBANGAN WEBSITE E-COMMERCE DAN GIS UNTUK MENDUKUNG PEMASARAN PRODUK KERAJINAN SERTA PARIWISATA BERBASIS KEARIFAN LOKAL DI DESA BALIAGA - Putra, Putu Maha; Prabandari, Luh Putu Cintya (STKIP PGRI Tulungagung, 2025)
The Bali Aga village possesses rich cultural heritage and significant local economic potential through traditional handicrafts and tourism rooted in local wisdom. However, limited access to digital marketing and information has become a major obstacle in optimizing these resources. This study aims to design and develop a web-based system that integrates e-commerce and Geographic Information System (GIS) to support the online marketing of handicraft products as well as interactive promotion of tourism destinations. The research methodology combines Design Thinking to explore user needs and Agile Development to enable iterative and adaptive system development based on user feedback. Data were collected through interviews, field observations, and literature studies, followed by system evaluation using Black Box Testing and User Acceptance Testing (UAT). The results show that the developed platform can effectively display local products online and provide an interactive digital map featuring tourism spots, travel routes, and supporting facilities. This system has proven effective in enhancing product visibility, expanding market reach, and providing tourists with accurate information about the village. In addition to producing a functional website, the study also contributes to improving local digital literacy through short training sessions. In conclusion, the integration of e-commerce and GIS offers an innovative solution to strengthen Bali Aga Village’s position as a leading cultural tourism destination while empowering the local economy based on traditional values in the digital era.